Industrial training final report : Sam Meerkat (M) Sdn. Bhd. / Ahmad Nazir Mohd Sobre - Mohd Sobre, Ahmad Nazir (Universiti Teknologi MARA (UiTM), 2024)
The company, which operates as a subsidiary of Singapore Aerospace Manufacturing Pte Ltd (SAM), benefits from the prestigious reputation of its parent company, which is acknowledged as a top producer of vital aero-engine components meeting the complex needs of the global aerospace market. Prominent aerospace original equipment manufacturers including Boeing, GE Aircraft Engines, GKN Aerospace Services, Goodrich, and others are among SAM's esteemed clients. The manufacturing industry is essential to fostering innovation and operational effectiveness in today's corporate environment. An extensive summary of my practical experience working in the assembly department of SAM Meerkat (M) Sdn. Bhd., a well- known company in the manufacturing sector, is included in this internship report. During my internship, SAM Meerkat's unique position as a leader in manufacturing excellence became clear, giving me a personal grasp of the complex procedures and commitment that go into the business's success. A prominent player in the manufacturing sector, SAM Meerkat (M) Sdn. Bhd. is well-known for its lengthy history and uncompromising dedication to quality. The business is positioned as a major player in the cutthroat manufacturing sector because to its operations, which embody an unrelenting quest of efficiency and quality. SAM Meerkat is a pioneer in the industry, producing innovative products and adhering strictly to quality control procedures. My internship gave me the chance to actively contribute to this history.